Modern Islamic thought in a radical age religious authority and internal criticism - Zaman, Muhammad Qasim (Cambridge University Press, 2012)
Among traditionally educated scholars, there is considerable disagreement on the crises that afflict modern Muslim societies, and the debates have grown more urgent since 9/11. Through an analysis of their work, both in the Arab Middle East and in India and Pakistan, this book explores some of the most fiercely debated issues - consensus, religious education, the position of women, socioeconomic justice, and jihad - facing the Islamic world today.